Building a Generation of Peace A Study of Peacefulness in Elementary School Students - Afriyati, Vira; Purnama Sari, Syska; Nellisa, Zahra; Diswantika, Noviana (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2024)
This study explores the concept of peace among elementary school students in Sumatra, Indonesia, with a focus on Aceh, Bandar Lampung, Palembang, and Bengkulu. Using qualitative methods with peace inventories, interviews, and image analysis, the study examined how children understand peace, especially the difference between “positive” and “negative” peace. The results showed that students generally associate peace with the absence of conflict and violence (negative peace). However, they also associated it with cooperation, harmony, kindness, freedom and justice (positive peace). The findings highlight the importance of peace education in shaping comprehensive understanding from an early age. The implications of this study emphasize the need for learning strategies that deeply embed peace values, so that schools can play a role in building a culture of peace among children.